Assessing Digital Literacy Among Young Professionals: A Research Mapping Review in the Context of Knowledge Workers - Zamrudi, Zakky; Wicaksono, Teguh; Melda, Melda; Zamilah, Ervica; Khuzaini, Khuzaini; Badjie, Gibriel (RSF Conference Series: Business, Management and Social Sciences, 2024)
This study examines the impact of digital transformation on knowledge workers, particularly young professionals, and their use of digital tools in the workplace. It addresses a gap in the literature by exploring how digital literacy affects adaptability, productivity, and job satisfaction in dynamic environments. Unlike previous studies that focus on educational settings or older knowledge workers, this research links digital literacy to employability, knowledge sharing, and innovation among young professionals. Using bibliometric analysis, the study identifies key themes such as digital literacy, knowledge management, and professional development. The findings show that digital literacy not only enables the use of new technologies but also fosters creativity and knowledge sharing, crucial in information-driven industries. The COVID-19 pandemic accelerated the need for digital adaptation, introducing challenges like technostress and information overload, which impact well-being and decision-making. This study underscores the importance of equipping young professionals with strong digital literacy to meet the demands of knowledge workers. It calls for organizations and educational institutions to prioritize digital skills training to bridge the digital divide and prepare the future workforce.